Pelatihan Brand Identity Sebagai Penguatan Promosi Digital Marketing bagi UMKM di Kabupaten Demak Jawa Tengah - Martina, Dannia Ayu; Kurdaningsih, Dian Marhaeni; Trimanah, Trimanah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service aims to increase the knowledge and skills of Small and Medium Enterprise (SME) actors in Sarwo Ijo Village, Demak regarding the importance of brand identity in strengthening digital marketing promotions. The methods used in this activity included socialization, training, and mentoring, with a focus on logo making, template design, and the Canva design application as a tool. This community service evaluation instrument used a questionnaire with a Likert scale and is analyzed using frequency distribution analysis techniques with SPSS. The evaluation results showed that socialization, training, and mentoring were effective in improving the understanding and skills of SME. Socialization succeeded in building participants' awareness and interest, while training provided applicable materials and practical skills in creating brand identity and digital marketing strategies. Post-training mentoring helped participants overcome obstacles, increase confidence, and ensure optimal strategy implementation. The program encourages SME to implement the concepts learned and strengthen their business competitiveness through brand identity. In addition, the result of this activity was the realization of several product logos and design templates that are ready to be used for promotion on social media and other digital platforms.